Studi Respon Siswa Terhadap Pengembangan Multimedia Interaktif Berbasis Chemo-Entrepreneurship Berbentuk Aplikasi Android - Kurnia, M. Riyo Agung; Haryanto, Haryanto; Sanova, Aulia; Dewi, Citra Ayu (Hydrogen: Jurnal Kependidikan Kimia, 2022)
Chemistry subject is a science that focuses students 1on understanding theÂ principles, theories, concepts and laws of chemistry and their application in realÂ life. Chemo-Entrepreneurship4(CEP) is an approach that links chemistry withÂ real objects. With this approach, students8are expected to be able to learn howÂ to process a material into a valuable and useful product and be able to foster anÂ entrepreneurial spirit. This study aims to develop interactive multimedia basedÂ on Chemo-Entrepreneurship in the form of an android application. The design ofÂ this study used the Lee & Owens model and involved 10 students of SMA NegeriÂ 10 Tanjung6Jabung Timur. The research instrument used in this study was aÂ questionnaire with analytical techniques in the form of qualitative data analysisÂ and quantitative data analysis. The results of this study include: 1) interactiveÂ multimedia developed is declared feasible by media experts and material experts,Â with a percentage score of 87.2% and 88.57% respectively, 2) interactiveÂ multimedia is declared feasible based on the teacher’s assessment with aÂ percentage a score of 91.4%, 3) get a percentage of student responses of 94%Â with a very good category. Thus, it can be concluded that the student response isÂ very positive to the chemo-entrepreneurship-based interactive multimedia thatÂ has been developed.